Automated router configuration using Java PHP / Noorul Asilah Osman - Osman, Noorul Asilah
Automated Router Configuration using JAVA PHP is a system application that allows users to automatically generate scripting configuration especially for IP Core services. The main objective of this project is to develop a system that address the problems faced by router (IP Core) users who have had long and difficult task to validate and configure scripting manually. With this application system, validation, verification and profiling information will be carried out easily without using the traditional method of using Excel file to manually extract the router configuration. Aside to that, scripting can be automatically generated and clearly displayed. This system is developed by using several programming languages such as Virtual Basic, PHP and Java for Web Application.